Affirmative Action As An Effort To Realize Justice For Poor Communities In Legal Aid Services - Bagus Rio Biantoro; Tunggul Anshari; Dhia Al Uyun (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
This article analyzes the application of affirmative action (AA), or the Right to Facilities and Special Treatment (Hak Kemudahan dan Perlakuan Khusus/HKPK), in the provision of legal aid for poor communities in Batu City through the perspective of John Rawls’s theory of distributive justice. This theory is used as the analytical framework because it emphasizes that justice cannot be realized merely through formal equality, but must also involve special treatment for disadvantaged groups so that they may obtain more equal opportunities. The absence of accredited Legal Aid Institutions or Legal Aid Organizations (LBH/OBH) domiciled in Batu City has the potential to impede poor communities’ access to legal aid. Therefore, the cooperation between the Batu City Government and LBH/OBH from outside the region is important to examine as a form of affirmative policy. This research uses a socio-legal method with a sociological-juridical approach. Data were obtained through interviews, observation, and questionnaires involving the Legal Section of the Batu City Regional Secretariat, seven LBH/OBH partners of the Batu City Government, and sixty users of the Among Warga Public Service Mall. The findings show that cooperation with LBH/OBH from outside the region constitutes a form of AA/HKPK implementation to expand access to legal aid for poor communities. However, its implementation still faces obstacles, including low public understanding, insufficient outreach, and the need to strengthen regulation and inter-institutional coordination. This article recommends optimizing legal aid through stronger public outreach, simplified access, the reopening of the Legal Aid Post at the Public Service Mall, and adjustment of regional regulations.